COMMUNICATIVE METHOD OF TEACHING ENGLISH TO NON- LINGUISTIC UNIVERSITY STUDENTS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
The article discusses the communicative method of teaching English to students of non-linguistic universities. The question is raised of some aspects of teaching English grammar to students of technical universities. The main attention is paid to the development of communicative skills and grammatical abilities with recommendations of grammatical tasks and other approaches aimed at the successful understanding of utterances in a foreign language.